Indicadores de Responsabilidad Social en el Gobierno Autónomo Descentralizado de la Provincia de Cotopaxi - Cabrera Zamora, Jéssica Marisol (2023)
At present, society and organizations in general seek a balance between competitiveness, success and social responsibility, which is why one of the strategies in the process of expansion is Corporate Social Responsibility. The general objective of the research was: Establish a set of CSR indicators, which contribute to the Public Management of the Department of Public Works of the Decentralized Autonomous Government of the Province of Cotopaxi, through the ETHOS Peru 2021 indicators. In the research to achieve more beneficial results, a mixed approach was used, in addition, it has a non-experimental descriptive scope, because it is based on diagnosing the daily activities that the institution performs or lacks.